PENGARUH LATIHAN FOOTWORK TWO-STEP TERHADAP KELINCAHAN KAKI PADA ATLET TENIS MEJA PUTRA MALAY PEKANBARU - Ronny, Muhammad; Vai, Aref; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The problem in this research is seen from serving the ball, in making basic strokes such as backhand and forehand. It's just that changing position on hitting the ball can be seen when making a serve, and on a smash this is still thought to be weak in the athlete's ability to use agility on the feet. move. This type of research is a kind of experimental research to see the effect of the shape of movement. The purpose of this research was to determine the effect of two-step footwork training on agility. The population in this study consisted of 6 male athletes of Malay Pekanbaru table tennis. The sampling technique uses total sampling, where the total population is sampled. The data collection technique was obtained from the pre-test and the post-test. The instrument in this s research used a side step test as an aid to determine foot dexterity. The analysis was performed using the t-test. Based on data analysis and discussion, it can be concluded that there is a significant effect of two-step footwork training on foot agility in male table tennis athletes in Pekanbaru, proven by the T-count of 6.603 and T- table of 2.015. Does that mean t> t table. At the level ɑ = 0.05.Key Words: Training Footwork Two-Steps, Dexterity Of The Feet, Table Tennis